THE EFFECT OF MARINATED TIME SPENT CINNAMON POWDER (Cinnamon burmannii) TO ORGANOLEPTIC QUALITY OF BALI BEEF - Y.K., BARATA; SRIYANI, N.L.P.; WIBAWA, A.A.P. (Majalah Ilmiah Peternakan, 2022)
The aim of this research is to determine the organoleptic quality of bali beef marinated by cinnamon powder for 0 hours, 4 hours, 8 hours and 12 hours. It was conducted in October 2020 - November 2020 at the Laboratory of Animal Product Technology and Microbiology Faculty of Animal Science, Udayana University. This studies used a Complete Random Design (CDR) with four treatments and four replications assessed by semi-trained 18 panelists. The four treatments were marinated bali beef with cinnamon powder for 0 hour (P0), marinated bali beef with cinnamon powder for 4 hours (P1), marinated bali beef with cinnamon powder for 8 hours (P2) and marinated bali beef with cinnamon powder for 12 hours (P3). The variables to consider is quality of organoleptic which is include colour, aroma, texture, flavour, tenderness, and overall acceptance. The results of this research have shown that the marinated time spent bali beef with cinnamon powder increased the colour, aroma, and overall acceptance value or significantly different (P<0,05) but, have no significant or different effect (P>0,05) with texture, flavour, and tenderness value. Based on the results of this research it can be concluded that the duration of marination of cinnamon powder (Cinnamon burmannii) can affect the organoleptic quality of bali beef. The length of marination for cinnamon powder that was most liked and accepted by the panelists was the length of marination for 4 hours as seen from the panelists’ assessment of the overall acceptance.